The Problem of Control of Membrane Vibrations with Non-Separated Multipoint Conditions at Intermediate Moments of Time - Barseghyan, V.R. (Кибернетика и вычислительная техника, 2019)
The purpose of the paper is to develop a constructive approach to construct a function of control action to control the vibrations of a rectangular membrane with given initial, final conditions and non-separated (non-local) values of the deflection and velocities of membrane points at intermediate moments of time. Results. By the method of separation of variables, the problem is reduced to the problem of control of ordinary differential equations with given initial, final, and non-separated multipoint intermediate conditions. Using the methods of the theory of control of finitedimensional systems with multipoint intermediate conditions, a control action to control vibrations of a rectangular membrane is constructed.